Transfusion Complications in Thalassemia: Patient Knowledge and Perspectives - Patterson, Sashoy; Singleton, Ashley; Branscomb, Jane; Nsonwu, Vivien; Spratling, Regena (Frontiers in Medicine, 2022)
Chronic transfusion, used to manage clinically significant forms of thalassemia, carries complication risks including iron overload, alloimmunization, and allergic or hemolytic reactions. Dissemination and implementation of evidence-based guidelines for minimizing these risks are complicated by the small numbers and increasing dispersion of the thalassemia population. This elevates patient’s role in understanding and communicating with providers about treatment. The present study sought to assess thalassemia patients’ knowledge of transfusion, complications, and guidelines; their experience of clinicians’ following guidelines; and their perspectives on ways to store and share personal transfusion data. A convenience sample of 32 patients participated in structured interviews. Most, if not all, understood iron overload, chelation therapy, blood typing, and cross-matching. Awareness of each of five of evidence-based transfusion guidelines that were discussed ranged from 72% to 88%. Patients expressed privacy concerns about each of three data storage options, slightly less for a registry than for a wallet card or smartphone app. The registry also avoided concerns that the other options placed extra burden on patients. Recommendations include increased education on the meaning and significance of packed, washed red blood cells, leuko-reduction, and detailed cross-matching, and implementation of a nationwide registry to make transfusion data available to providers anywhere at the point of care. Registry implementation should be sensitive to patients’ privacy and security concerns, but also help them appropriately weigh those against safety benefits. These actions could help reduce transfusion complications in thalassemia by improving patient efficacy and increasing adherence to evidence-based guidelines.